Iron-Rich Diagenetic Minerals are Biomarkers of Microbial Activity in Antarctic Rocks - Wierzchos, Jacek; Ascaso, Carmen; García-Sancho, Leopoldo; Green, Allan (Taylor & Francis, 2003)
10 pages, figures, and tables statistics. The cold, dry ecosystems of Antarctica have been shown to harbor traces left behind by microbial activity within certain types of rocks, but only two indirect biomarkers of cryptoendolithic activity in the Antarctic cold desert zone have been described to date. These are the geophysical and geochemical bioweathering patterns macroscopically observed in sandstone rock. Here we show that in this extreme environment, minerals are biologically transformed, and as a result, Fe-rich diagenetic minerals in the form of iron hydroxide nanocrystals and biogenic clays are deposited around chasmoendolithic hyphae and bacterial cells. Thus, when microbial life decays, these characteristic neocrystalized minerals act as distinct biomarkers of previous endolithic activity. The ability to recognize these traces may have potential astrobiological implications because the Antarctic Ross Desert is considered a terrestrial analogue of a possible ecosystem on early Mars. Peer reviewed